Personal autonomy : philosophy and literature - Vice, Samantha Wynne (Rhodes University, Faculty of Humanities, Department of Philosophy, 1999)
Gerald Dworkin's influential account of Personal Autonomy offers the following two conditions for autonomy: (i) Authenticity - the condition that one identify with one's beliefs, desires and values after a process of critical reflection, and (ii) Procedural Independence - the identification in (i) must not be "influenced in ways which make the process of identification in some way alien to the individual" (Dworkin 1989:61). I argue in this thesis that there are cases which fulfil both of Dworkin's conditions, yet are clearly not cases of autonomy. Specifically, I argue that we can best assess the adequacy of Dworkin's account of autonomy through literature, because it provides a unique medium for testing his account on the very terms he sets up for himself - ie. that autonomy apply to, and make sense of, persons leading lives of a certain quality. The examination of two novels - Kazuo Ishiguro's The Remains of the Day and Henry James's The Portrait of a Lady - shows that Dworkin's explanation of identification and critical reflection is inadequate for capturing their role in autonomy and that he does not pay enough attention to the role of external factors in preventing or supporting autonomy. As an alternative, I offer the following two conditions for autonomy: (i) critical reflection of a certain kind - radical reflection, and (ii) the ability to translate the results of (i) into action - competence. The novels demonstrate that both conditions are dependent upon considerations of the content of one's beliefs, desires, values etc. Certain of these will prevent or hinder the achievement of autonomy because of their content, so autonomy must be understood in relation to substantial considerations, rather than in purely formal terms, as Dworkin argues.
Keywords: Autonomy (Philosophy); Ishiguro, Kazuo, 1954- -- Remains Of The Day; James, Henry, 1843-1916. Portrait of a lady